Self-contacting Cys, Ser, and Thr residues in high-resolution protein crystal structures: Tertiary constraints or hydrogen bonds? - Singh P.; Ramanathan V.; Sankararamakrishnan R. (My University, 2025)
Functional groups in the side-chains of at least 10 amino acids are mainly involved in tertiary interactions. However, structural and functional significance of intra-residue interactions has not been fully recognized. In this study, we have analyzed ~5800 non-redundant high-resolution protein structures and identified 1166 self-contacts between the side-chain S-H/O-H and backbone C=O groups in Cys, Ser, and Thr residues that satisfied the geometric criteria to form hydrogen bonds. Quantum chemical calculations using model compounds were used to evaluate single point energy for 45 representative examples from different allowed regions of Ramachandran map. Relative energy profiles obtained by varying the side-chain dihedral angle χ1 revealed that the energy difference between the crystal structure and the minimum energy conformations is between 0 and 3 kcal/mol. Natural bond orbital analysis (NBO) of self-contacting Cys residues revealed no charge transfer between Cys side-chain S-H and the backbone C=O groups. However, side-chain hydroxyl and the backbone C=O groups of 90%–95% of all self-contacting Ser and Thr residues are involved in charge transfer and the second order perturbation energy of majority of them is above 1 kcal/mol. Interaction energies calculated for model compounds along with NBO and NCIPLOT analyses demonstrate that the self-contacts observed in Ser and Thr residues can be described as hydrogen bonds. These interactions may provide stability to the loop/coil conformations. Self-contacting Cys residues are buried and the self-contacts appear to be mostly due to tertiary constraints. Dispersion between the self-contacting groups is one way to explain the close approach in Cys residues. Mutation studies will further validate and reveal the structural and functional significance of these self-contacting residues. © 2024 The Protein Society.